Influences of Different Sowing Dates on Growth and Yield of Linum usitatissimum L. at Sheringal, Dir Upper, Khyber Pakhtunkhwa, Pakistan - Haq, Syed Manzoor ul (Darul Yasin Al Sys, 2023)
The present experiment was conducted to examine the influence of the seeds sowing date on parameters like height of plant, number of the fruiting branches per flax plant, number of capsules, quantity of seeds per flax plant, weight (g) of (1000) seed of the Linseed (Linum usitatissimum L.) at the Sheringal, Dir Upper, Khyber Pakhtunkhwa, Pakistan. Experiment was designed in randomized complete block, consisting of three partitions. The sowing times of the plots were kept (1st February, 15th February and 1st March). The characters studied were the number of branches bearing fruit per plant, number of capsules per flax plant, seed number per capsule, plant height, and 1000 seeds weight. The data revealed that, sowing time has an important impact on height of the plant, numbers of capsules per plant and on the quantity of seeds in each pod. Mean comparison indicated that sum of the main fruiting branches of plant, number of capsule per plant, seeds number per pod in flax, plant height (cm), and 1000 flaxseeds weight were at the highest level observed in second sowing date (15th February). It was also noted that sowing date executed a positive change on all traits. The results showed that the yield of 1st February, 15th February and 1st March for number of seeds/capsule were 6.07, 6.20 and 5.18; likewise the parameter of 1000 seeds weight 7.31 g, 8.26 g and 6.03 g. It was concluded that early sowing period had a positive effect on all the parameters studied.